Does Intellectual Capital Affect The Directorate General Of Taxes Organisational Performance? - Yusrifalda, Amalia; Darmawan, Davi Judha; Firmansyah, Amrie (WIM Solusi Prima, 2024)
Intellectual capital is one of the important capital assets that every private and public sector organization should properly manage. Intellectual capital refers to individuals' knowledge, skills, and innovations within an organization. It can create a competitive advantage and improve organizational performance when managed effectively. Optimal management of intellectual capital is particularly important in the public sector, as it can strengthen institutional capacity to deliver more efficient and effective public services, ultimately increasing citizen satisfaction. With the development of literature studies related to intellectual capital, it is found that testing conducted in the public sector is still limited. This research examines intellectual capital's influence on the performance of the public sector organization, specifically the Directorate General of Taxes. This research uses the Partial Least Square-Structural Equation Modeling analysis technique based on primary data sourced from an online questionnaire survey of employees of the Directorate General of Taxes from various levels of positions at Tax Service Offices in the DKI Jakarta area and its surroundings and a sample of 52 observations was obtained. The research concludes that public structural and relational capital positively impact organizational performance. Meanwhile, public human capital does not influence organizational performance. This study is expected to contribute to developing theory and practice not only to intellectual capital as an intangible asset but also to human resource management, organizational infrastructure, and external relations in the context of public services. In addition, the findings of this study can serve as a basis for formulating policies and actions that can improve the effectiveness and efficiency of public institutions, as well as encourage further discussion regarding the management of intellectual capital to achieve more sustainable public sector organizational goals.